2002
DOI: 10.1002/jca.10032
|View full text |Cite
|
Sign up to set email alerts
|

Maximal flow rates and sieving coefficients in different plasmafilters: Effects of increased membrane surfaces and effective length under standardized in vitro conditions

Abstract: In Europe, capillary membrane filters are the favored method for plasmapheresis and detoxification systems including a plasma separation unit. Using capillary membrane filters clearance depends on the filtration rate and the sieving coefficient (Qs) for the plasma substrates. We investigated whether the increase of the effective membrane surface of plasmafilters enables higher clearance rates than a small plasmafilter. Heparinized porcine blood (5 I.U./l) of healthy pigs was used for an in vitro circuit. Filte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…We have previously reported that the SC of each substance by SePE was as follows: TNF‐α, 0.99; Alb, 0.73; IgG, 0.50; coagulation factor XIII (FXIII), 0.17; and Fib, 0.0; respectively . The SCs of plasma proteins and Fib by PE were approximately 1.00 . Therefore, compared with PE, a larger amount of PV should be processed during SePE for improving the removal of IgG.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that the SC of each substance by SePE was as follows: TNF‐α, 0.99; Alb, 0.73; IgG, 0.50; coagulation factor XIII (FXIII), 0.17; and Fib, 0.0; respectively . The SCs of plasma proteins and Fib by PE were approximately 1.00 . Therefore, compared with PE, a larger amount of PV should be processed during SePE for improving the removal of IgG.…”
Section: Discussionmentioning
confidence: 99%
“…This disparity is not surprising as it is well known that the experimental design for research on membranes and filters is quite often unrelated to the modes of operation that are encountered during clinical applications. 4,5,14 Therefore, it would be important to provide a single method that allows visualization of flow distribution under all study conditions from in vitro to clinical application. As shown here, thermography systems could meet this demand because of a filter perfusion-related development of surface temperature profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Using a clinically proven apheresis unit (AK10, Gambro, Germany), a recirculating in vitro circuit was assembled (Figure 1a) according to the whole blood in vitro system described previously. [12][13][14][15] The specifications for the hemofilter (type: only for experimental use) were as follows -membrane: polyacrylonitrile, surface: 1.8 m 2 ; effective length 18 cm; housing material: acrylonitrile styrene copolymer and polycarbonate; Ca. Asahi.…”
Section: Renal Replacement Therapy In Vitro Circuitmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that an increased tendency of RBCs for aggregation promotes the stasis of blood and can lead to blocked fibers. As low blood flow velocities support cell aggregation and even sedimentation, we concluded that increases in the membrane surface area (which are usually achieved by a combination of increased number and length of the hollow fibers) may deteriorate the overall situation . Using our in vitro model, we compared three plasmafilters as this membrane process/filter type is most vulnerable for insufficient blood flow rates.…”
Section: Third Step: An Increased Membrane Surface Affects Filter Blomentioning
confidence: 99%